The academic and Non-academic factors related to subject failing in the school of arts faculty of sciences and humanities of the University of El Salvador, semester I -2000 - Mata, Miguel Angel; Portillo, Norma Alicia; Tobar, Glenda Magaly (San Salvador : Universidad de El Salvador, 2002)
Imídeo G. Nérici (1985) points out in his book, “Hacia una Didáctica General Dinámica”, that university teaching should avoid four things. First of all, university studies should not only aim to prepare students to pass exams. Second, university students should not limit themselves to just take notes and then memorize them. Third, university students should neither play passive roles nor limit themselves to know just what the teacher gives them. Fourth, university students should not be kept away from the problems their community and country face. The four aspects mentioned above can be closely related to the academic factors that might have influenced subject failing at the School of Arts The University of El Salvador in semester I-2000. Attrition cases were not included because in the data collection there was only one case. These pages contain the final report in which the aim was to find out the academic and non-academic factors related to students’ subject failing of the School of Arts of the University of El Salvador in Semester I-2000
Incluye anexos
Tesis (Licenciatura en Idiomas) -- Universidad de El Salvador, San Salvador, 2002
Keywords: Deserción universitaria; Escuela de artes; Rendimiento académico bajo